Predictors of PTSD Treatment Response Trajectories in a Sample of Childhood Sexual Abuse Survivors: The Roles of Social Support, Coping, and PTSD Symptom Clusters - Fletcher, Shelley (Journal of interpersonal violence, 2021)
This study aimed to (a) identify posttraumatic stress disorder (PTSD) trajectories in a sample of Danish treatment-seeking childhood sexual abuse (CSA) survivors and (b) examine the roles of social support, coping style, and individual PTSD symptom clusters (avoidance, reexperiencing, and hyperarousal) as predictors of the identified trajectories. We utilized a convenience sample of 439 CSA survivors attending personalized psychotherapy treatment in Denmark. Four assessments were conducted on a six monthly basis over a period of 18 months. We used latent class growth analysis (LCGA) to test solutions with one to six classes. Following this, a logistic regression was conducted to examine predictors of the identified trajectories. Results revealed four distinct trajectories which were labeled high PTSD gradual response, high PTSD treatment resistant, moderate PTSD rapid response, and moderate PTSD gradual response. Emotional and detached coping and more severe pretreatment avoidance and reexperiencing symptoms were associated with more severe and treatment resistant PTSD. High social support and a longer length of time since the abuse were associated with less severe PTSD which improved over time. The findings suggested that treatment response of PTSD in CSA survivors is characterized by distinct patterns with varying levels and rates of PTSD symptom improvement. Results revealed that social support is protective and that emotional and detached coping and high pretreatment levels of avoidance and reexperiencing symptoms are risk factors in relation to PTSD severity and course. These factors could potentially identify patients who are at risk of not responding to treatment. Furthermore, these factors could be specifically addressed to increase positive outcomes for treatment-seeking CSA survivors.